2017
DOI: 10.1002/ecj.11949
|View full text |Cite
|
Sign up to set email alerts
|

Arousal Retention Effect of Magnetic Stimulation to Car Drivers Preventing Drowsy Driving without Sleep Rebound

Abstract: SUMMARY We report experimental validation of the existence of so‐called the sleeping rebound phenomenon against each sensory stimulus using a driving simulator and the electroencephalograph for about 105 subjects with evaluation of an arousal index (α + β)/(δ + θ) in the electroencephalogram measurements after each driving operation. We found that methods using the perfume presentation, the alert presentation, the vibration, and chewing gum were resulted in the sleeping rebound phenomenon, while a proposed mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In the previous studies of Yoshida et al [12] and Mohri et al [13], to maintain a high arousal level, the effects of several stimulation methods, such as the use of a fragrance, alarm, and shoulder oscillation, were confirmed. As a result, the sleeping rebound occurred 10 min after the stimulation in those studies.…”
Section: Consideration Of Thermal Stimulation For High Arousal Levelsmentioning
confidence: 77%
See 1 more Smart Citation
“…In the previous studies of Yoshida et al [12] and Mohri et al [13], to maintain a high arousal level, the effects of several stimulation methods, such as the use of a fragrance, alarm, and shoulder oscillation, were confirmed. As a result, the sleeping rebound occurred 10 min after the stimulation in those studies.…”
Section: Consideration Of Thermal Stimulation For High Arousal Levelsmentioning
confidence: 77%
“…In previous studies, it was shown that the thermal comfort of occupants was immediately changed in accordance with changes in the indoor ambient temperature [11]. The arousal level was increased by outer stimulation and was maintained at a high state for several minutes [12,13]. Based on these results of previous studies, we hypothesized that thermal stimulation due to cooling can improve the arousal level of occupants.…”
Section: Introductionmentioning
confidence: 77%
“…Some researches concentrated on the direct electric current transcranial stimulation and found that it could be a useful fatigue countermeasure and may be more beneficial than caffeine since boosts in performance and mood last longer time [20]. Other authors used sophisticated means to stimulate the spine by using a static magnetic field with a spatial alternation of poles that prevented drowsiness without invoking the REM rebound phenomenon [21]. The latter, however, appeared with many other methods of stimulating vigilance and attention.…”
Section: State Of the Artmentioning
confidence: 99%
“…Thus, constant control of indoor temperature does not lead to improvement in both thermal comfort and arousal level of driver. Several previous studies found that thermal comfort changes instantaneously with changes in indoor temperature (10) (11) , while arousal is maintained to some extent even after external stimuli are removed (12) (13) . Based on these findings, we hypothesized that both thermal comfort and arousal can be improved by appropriately changing the indoor temperature, and tested this hypothesis in several thermal environmental conditions in our previous studies (14) (15) (16) .…”
Section: Introductionmentioning
confidence: 96%